Direct Determination of Absolute Configuration of Methyl-Substituted Phenyloxiranes: Combined Experimental and Theoretical Approach - Fristrup, P.; Lassen, P.; Johannessen, C.; Tanner, D.; Norrby, P.; Lars, H.; Jalkanen, Karl (American Chemical Society, 2006)
Three possible methyl-substituted phenyloxiranes have been synthesized in enantioenriched form (89-99% enantiomeric excess (ee)), and their vibrational absorption (VA) and vibrational circular dichroism (VCD)spectra have been recorded. The experimental spectra are compared to theoretical spectra obtained from quantum mechanical calculations (density functional theory with the B3LYP hybrid exchange correlation functional with 6-31++G**, aug-cc-pVDZ, or aug-cc-pVTZ basis set) and related to the physical structure of the compounds. The absolute configuration could be established directly in each case by comparing experimental and theoretical spectra. In addition, we have been able to document the changes that occur both in structures and in the VA and VCD spectra due to substituent effects on the oxirane ring.